Silver nanoparticles incorporated with enzymatically derived chitooligosaccharides: preparation, characterization, and biological potential evaluation - Affes, Sawsan; Aranaz, Inmaculada; Acosta, Niuris; Heras, Ángeles; Nasri, Moncef; Maalej, Hana (Frontiers in Food Science and Technology, 2024)
In this work, silver nanoparticles (AgNPs) were elaborated using a simple, low-cost, and reproducible method by thermal treatment at 90°C of chitooligosaccharides (COSs), produced by chitosan depolymerization using the digestives chitosanases from Portunus segnis viscera, in the presence of AgNO3. The characterization of the obtained AgNPs, using UV–visible spectroscopy, transmission electron microscopy (TEM), dynamic light scattering (DLS), and Fourier-transform infrared (FTIR) spectroscopy analyses, showed that they are crystalline, spherical and stable for a month at 4°C. Moreover, the biological properties of the synthesized AgNPs were evaluated, proving that they exhibited interesting antioxidant and antibacterial activities. The present investigation suggested that COSs will be a good source for the preparation of AgNPs that could be useful in different industrial and biomedical applications.